Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5588/ijtld.15.0696
|View full text |Cite
|
Sign up to set email alerts
|

Xpert<SUP>®</SUP> MTB/RIF detection of rifampin resistance and time to treatment initiation in Harare, Zimbabwe

Abstract: Background Patients at elevated risk of drug-resistant tuberculosis are prioritized for testing with Xpert MTB/RIF® (“Xpert”), though clinical utility in this population is understudied. Design From November 2011 to June 2014, consecutive outpatients with history of prior tuberculosis in high-density suburbs of Harare, Zimbabwe were tested with Xpert, solid and liquid culture, and the microscopically-observed drug susceptibility assay. Diagnostic accuracy for rifampin-resistance and time to second-line regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Our results and the review of six studies performed in other developing countries from Africa and Asia indicate that the most common mutations conferring RR are located in the region of Probe E, followed by Probe B and Probe D, while mutations in the region of Probe A and Probe C were less common [ 8 13 ]. The predominance of Probe E and the fact that the Xpert assay does not provide information of specific mutations in the rpoB gene limit its value as an epidemiological tool to study RR-TB.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our results and the review of six studies performed in other developing countries from Africa and Asia indicate that the most common mutations conferring RR are located in the region of Probe E, followed by Probe B and Probe D, while mutations in the region of Probe A and Probe C were less common [ 8 13 ]. The predominance of Probe E and the fact that the Xpert assay does not provide information of specific mutations in the rpoB gene limit its value as an epidemiological tool to study RR-TB.…”
Section: Discussionmentioning
confidence: 70%
“…The PubMed search strategy showed 47 studies, and 41 were excluded because they did not provide information about the probes that conferred RR. Finally, six studies were included in the analysis [ 8 13 ]. The results of these studies and our study are compared in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xpert is one of the most widely used tests for TB and drug-resistance 9 , 34 and although it is a significant advancement, time-to-treatment – especially for MDR- and XDR-TB - is still very long 35 38 . Our results show that accurate second-line drug testing using MTBDR sl is possible on CE from Xpert cartridges that would otherwise be discarded.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a report from Haiti, 86.9% of patients with rifampin resistance detected by the Xpert®MTB/RIF were later proved to have MDR-TB due to simultaneous resistance to isoniazid (INH) [8], while a report from Zimbabwe found that 85.2% of patients detected with the Xpert®MTB/RIF as resistant to rifampin were actually MDR [9].…”
Section: Discussionmentioning
confidence: 99%